Teachers' perceptions of applying information technology in English language teaching - a case at Quang Xuong one High school, Thanh Hoa province - Nguyễn, Thị Hương (ĐHNN, 2017)
Information Technology in English Language Teaching. Information Technology in Vietnamese ELT. Teachers‟ perceptions of IT and using IT in ELT. Teachers‟ opportunities for using IT in teaching English in the classroom. Teachers' challenges in using IT in ELT. eachers‟ suggested solutions to enhance the effectiveness of using IT in ELT.